Power Quality Improvement Using UPQC for Grid Interconnected Renewable Energy Sources - Kannan, R. (Institute of Electrical and Electronics Engineers Inc., 2021)
In most of the renewable energy sources power electronics devices are incorporated which introduce harmonics in grid connected system. In this paper, renewable energy sources are interconnected to grid by means of smart voltage source inverter which reduces harmonics. The main objective of this proposed work is to reduce Total Harmonic Distortion (THD). The smart voltage source inverter using Unified Power Quality Conditioner (UPQC) injects the power to the grid from photovoltaic sources to compensate reactive power demand. The effectiveness of the proposed schemes is demonstrated using MATLAB Simulink and provides better THD of grid connected Photovoltaic UPQC (PVUPQC). Â© 2021 IEEE.